Getting back to work after injury: the UK Burden of Injury multicentre longitudinal study - Kendrick Denise; Vinogradova Yana; Coupland Carol; Christie Nicola; Lyons Ronan A; Towner Elizabeth L (BMC, 2012)
Abstract Background Injuries to working age adults are common and place a considerable burden on health services accounting for more than 10% of GP sick notes and 14% of those claiming benefits because they are unable to work in the UK. General practitioners (GPs) currently assess fitness to work and provide care and referral to other services to facilitate return to work (RTW). Recent UK recommendations suggest replacing GP sickness certification with independent assessments of fitness to work after four weeks sick leave. The impact of a wide range of injuries on RTW and subsequent need for independent fitness to work assessments has not been well studied in the UK. The aim of this study was to quantify RTW and factors predicting RTW following a wide range of injuries. Methods We used a multicentre longitudinal study, set in four acute NHS Trusts in the UK which recruited emergency department (ED) attenders and hospital admissions for injury and included those aged 16-65years that were employed or self-employed before the injury. Participants were followed up by postal questionnaire at 1, 4 and 12 months post injury to measure health status (EQ-5D), recovery, use of health and social services, time off work in the preceding month and work problems amongst those who had RTW. Multivariable Poisson regression with a robust variance estimator was used to estimate relative risks for factors associated with RTW. Results One month after injury 35% of ED attenders had fully RTW. The self employed were more likely (RR 1.70, 95% CI 1.17 to 2.47 compared with employed) and the moderate/severely injured less likely to RTW (RR 0.48, 95% CI 0.32 to 0.72 compared with minor injuries). At four months, 83% of ED attenders had RTW and self employment and injury severity remained significant predictors of RTW (self employment RR 1.15, 95% CI 1.03 to 1.30; moderate/severe injury RR 0.79, 95% CI 0.68 to 0.92). At four months 57% of hospital admissions had RTW. Men were more likely than women to RTW (RR 1.94, 95% CI 1.34 to 2.82), whilst those injured at work (RR 0.49, 95% CI 0.27 to 0.87 compared with at home) and those living in deprived areas (most deprived tertile RR 0.59, 95% CI 0.40 to 0.85 and middle tertile RR 0.61, 95% CI 0.40 to 0.93) were less likely to RTW. Health status was significantly poorer at one and four months after injury than before the injury and was significantly poorer amongst those that had not RTW compared to those that had. Problems with pain control, undertaking usual activities, mobility and anxiety and depression were common and persisted in a considerable proportion of participants up to four months post injury. Conclusions Injuries have a large impact on time off work, including amongst those whose injuries did not warrant hospital admission. The majority of injured people would require an in-depth fitness for work assessment if recent UK recommendations are implemented. Many people will have on-going pain, mobility problems, anxiety and depression at the point of assessment and it is important that patients are encouraged to use primary care services to address these problems. A range of factors may be useful for identifying those at risk of a slower recovery and a delayed RTW so that appropriate interventions can be provided to this group.